ANALISIS NILAI TAMBAH PENGOLAHAN PISANG CAVENDISH (Musaa cuminata) MENJADI BOLU PISANG (STUDI KASUS PT. TRANS RETAIL INDONESIA, MEDAN FAIR) - Mey Linda Sipayung; Asmina H. Sinaga; Tiurmaida Nainggolan; Widya Lestari (JURNAL AGROPLASMA, 2021)
This study aims to: (1) determine the process of processing cavendish banana (Musa acuminata) into banana sponge in the study area, (2) knowing the added value generated from the processing of cavendish banana (Musa acuminata) into banana sponge in the study area, (3 ) know the internal and external factors that are strengths, weaknesses, opportunities and threats in the development of cavendish banana processing (Musa acuminata) into banana sponge in the research area and (4) find out what alternatives and priorities can be applied in the development of cavendish banana processing (Musa acuminata) becomes a banana sponge in the study area. This research was conducted at PT. Trans Retail Indonesia, Medan Fair The determination of the research area was carried out purposively. The data collection method uses a questionnaire. Data analysis was performed descriptively and SWOT analysis. The results showed the process of making banana sponge begins with stripping bananas, followed by the process of mixing, then printing, steaming, cooking, cooling and packaging. The added value of the average processing of cavendish banana into a banana sponge is Rp 97,662.42, with an added value ratio of 46.66% <50% meaning that the added value is relatively low. The internal factors in the development of processing banana cavendish into banana sponge in the study area are the strength factor: 18.20% due to easily obtainable raw materials, 15.30% due to affordable sponge prices and 15.80% due to the easy making of banana sponge. The weakness factor of the development of banana sponge in the study area is 16.30% because the raw material of bananas is easy to rot, 17.40% because the banana sponge is not durable and 17% because with a banana that is too ripe can make the resulting banana sponge too sweet, making it less preferred . External factors consist of the chance that 17.1% of the business opportunity for processing cavendish banana into a banana sponge is due to the high demand of consumers, especially children, 13.90% because similar products are not available around the place, 16.90% because raw materials can be made into another new product. The threat factor to the development of cavendish banana processing into banana sponge is 17.20% because there are other products that are of interest to consumers, 17% because many other food businesses are around the business and 17% because they are far from residential areas. Alternative and priority strategies that must be done by the company, the S-O that has been formulated, namely: keeping prices affordable to maintain market share. Keywords: added value and cavendish banana, banana sponge and SWOT